ANALYSIS OF THE FINANCIAL MANAGEMENT PERFORMANCE OF TATAH MOSQUE VILLAGE, BARITO KUALA REGENCY - Hikmahwati; Alfina Damayanti; Rizky Amelia (ZILLZELL MEDIA PRIMA, 2024)
The Tatah Mesjid Village Government is obliged to carry out reporting and accountability for the implementation of the Village APBD. The Budget Realization Report shows that the financial performance of the Tatah Mesjid Village Government, Barito Kuala Regency is running well, but the success of the budget performance that has been achieved does not necessarily fully implement the value for money principle (economic, efficient and effective) so it is necessary to measure the achievement of the Village APBD performance. This research aims to measure the financial management performance of the Tatah Mesjid Village Government, Barito Kuala Regency using the value for money concept for the 2020-2022 fiscal year. The research method uses quantitative with a descriptive approach. Data was analyzed using the concept of value for money to measure economic ratios, efficiency and effectiveness. The research results show that the financial performance of the Tatah Mesjid Village government during 2020-2022 for economic measurements consistently shows results >100% with economic criteria. The efficiency measurement for the 2021 fiscal year of 97.07% is included in the efficient criteria because it is between 90-99%, however in 2020 and 2022 the results show inefficiency because the ratio is more than 100%. Measuring the effectiveness of village funds and allocation of village funds shows effective results. However, tax and levy revenue sharing shows less effective results because the ratio is <65%.